A systemic linguistic analysis of process types, participant roles and modality types in Obama's speeches on Muslim world issues / Fatma M .Farhat - Fatma, M. Farhat (2016)

(untitled)
In the last five years, the political discourse of President Barack Obama has attracted a great number of researchers and students in Linguistics and Social Studies around the world. The discourses through which Obama addressed the issues encountered by the Muslim World which have been central in the political world, still require more investigations and linguistic analysis. The current study is dedicated to investigate the political discourse of President Obama which embodies Islamic world issues, applying the Hallidayan Systemic Functional Linguistics (SFL) as the theoretical framework to study language structure and function. Specifically, the study will apply the SFL theory as introduced by Halliday (1985-1994) and reintroduced by Halliday and Matthiessen (2004 2014). The principle aim of the current study is to expose the representation of the issues in the discourse of President Barack Obama through its Transitivity processes and Modality patterns. Six speeches by the President sourced from the White House website (http://www.whitehouse.gov/), the archive of President Obama‟s speeches are used as data. The study applies a qualitative method to analyze the data. The results show that the president mobilizes various types of Transitivity processes and participants, and Modality types in order to express his views. His linguistic devices of Transitivity and Modality featured within his speeches on the Muslim world issues can be a good linguistic account to understand his construction of these issues.